FAKTOR-FAKTOR YANG MEMPENGARUHI PENGUNGKAPAN CORPORATE SOCIAL RESPONSIBILITY (STUDI EMPIRIS PERUSAHAAN SEKTOR ENERGY DAN SEKTOR BASIC MATERIALS) - Mitha Rahayu Safira; Ferdawati Ferdawati; Gustati Gustati (Journal of Applied Accounting And Business, 2025)
This study aims to empirically prove the influence of foreign ownership, profitability, company age and company size on Corporate Social Responsibility disclosure. The data used in this study are secondary data obtained from annual reports and company sustainability reports. This research focuses on companies engaged in the energy sector and the basic materials sector listed on the indonesia stock exchange for the period 2021 to 2023. The sampling technique used purposive sampling method. To test the research hypothesis, multiple linear regression analysis was conducted using spss version 25. The results showed that foreign ownership and profitability had no effect on Corporate Social Responsibility disclosure, while company age and company size had a positive effect on Corporate Social Responsibility disclosure. Companies that have been established for a long time tend to have a lot of experience in Corporate Social Responsibility disclosure. Meanwhile, large company size motivates management to utilize the trust of stakeholders and the surrounding community to disclose more extensive Corporate Social Responsibility. This study can provide a deeper understanding of the factors that influence Corporate Social Responsibility disclosure, which can serve as a reference for regulators in designing more effective corporate policies.